Tlingit burial boxes with carvings, Wrangell, Alaska, in engraving made ca. 1875 - University of Washington Libraries
Photograph of engraving (after photograph by Peterson Bros.) of cedar structures, several with carvings Image from Harper's Weekly, Oct. 4, 1879, p. 792 Note from unidentified source: Indian burial ground at Fort Wrangle